PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SMP - Hilmi Hidayatulloh Poetra Azhar; Istikomah Istikomah (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Principal leadership plays a crucial role in improving the quality of national education, but is often hampered by a purely administrative approach. This study focuses on an in-depth analysis of the principal's strategic role in improving teacher professionalism at SMPN 2 Jabon by identifying various indicators of effective and adaptive leadership. Using a descriptive qualitative approach, the research was systematically implemented, including data collection through field observations, in-depth interviews with school stakeholders, and documentation studies, which were then analyzed using the interactive model of Miles, Huberman, and Saldana. The results revealed that leadership effectiveness in this institution is realized through the systematic integration of transformational, instructional, and participatory styles. Key findings indicate a significant improvement in the aspects of sustainable teacher competency development, stable work motivation, and the implementation of a more transparent and constructive performance evaluation system. A humanistic leadership style oriented towards empowering human resources has been proven to create a conducive work climate and accelerate pedagogical innovation among educators. The main conclusion of the study confirms that the figure of a principal who is able to adapt various leadership styles according to the unique context of the school makes a major contribution to strengthening teacher professionalism and improving the quality of school education in order to create a superior generation that has character, is intelligent, competitive, and is ready to face all the dynamics of the global era. ABSTRAK Kepemimpinan kepala sekolah berperan krusial dalam mendongkrak mutu pendidikan nasional, namun sering kali masih terkendala oleh pendekatan yang bersifat administratif semata. Penelitian ini berfokus pada analisis mendalam mengenai peran strategis kepala sekolah dalam meningkatkan profesionalisme guru di SMPN 2 Jabon melalui identifikasi berbagai indikator kepemimpinan yang efektif dan adaptif. Dengan menggunakan pendekatan kualitatif deskriptif, tahapan penelitian dilaksanakan secara sistematis meliputi pengumpulan data melalui observasi lapangan, wawancara mendalam dengan pemangku kepentingan sekolah, serta studi dokumentasi yang kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Hasil penelitian mengungkap bahwa efektivitas kepemimpinan di institusi ini terwujud melalui integrasi gaya transformasional, instruksional, serta partisipatif secara sistematis. Temuan utama menunjukkan adanya peningkatan nyata dalam aspek pengembangan kompetensi guru yang berkelanjutan, motivasi kerja yang stabil, serta implementasi sistem evaluasi kinerja yang lebih transparan dan konstruktif. Gaya kepemimpinan yang humanis serta berorientasi pada pemberdayaan sumber daya manusia terbukti mampu menciptakan iklim kerja yang kondusif sekaligus memicu akselerasi inovasi pedagogik para pendidik. Simpulan utama penelitian menegaskan bahwa figur kepala sekolah yang mampu mengadaptasi berbagai gaya kepemimpinan sesuai konteks unik sekolah memberikan kontribusi besar terhadap penguatan profesionalisme guru dan perbaikan mutu pendidikan sekolah demi terciptanya generasi unggul yang berkarakter, cerdas, kompetitif, dan siap menghadapi seluruh dinamika zaman global.